Cycle-Inhibiting Factor Is Associated with Burkholderia pseudomallei Invasion in Human Neuronal Cells - Amporn Rungruengkitkun; Niramol Jitprasutwit; Watcharamat Muangkaew; Chantira Suttikornchai; Sarunporn Tandhavanant; Nitaya Indrawattana; Sumate Ampawong; Passanesh Sukphopetch; Narisara Chantratita; Pornpan Pumirat (Biology, 2022)
Burkholderia pseudomallei is a pathogenic bacterium that causes human melioidosis, which is associated with a high mortality rate. However, the underlying mechanisms of B. pseudomallei pathogenesis are largely unknown. In this study, we examined the infection of human neuronal SH-Sy5y cells by several clinically relevant B. pseudomallei strains. We found that all tested B. pseudomallei strains can invade SH-Sy5y cells, undergo intracellular replication, cause actin-tail formation, and form multinucleated giant cells. Additionally, a deletion mutant of B. pseudomallei cycle-inhibiting factor (cif) was constructed that exhibited reduced invasion in SH-Sy5y cells. Complementation of cif restored invasion of the B. pseudomallei cif-deleted mutant. Our findings enhance understanding of B. pseudomallei pathogenicity in terms of the virulence factor Cif and demonstrate the function of Cif in neurological melioidosis. This may eventually lead to the discovery of novel targets for treatment and a strategy to control the disease.